NILAI PO SAPO ESEMPAY (KESETIAKAWANAN) DAN SOKKLA (KEAGAMAAN) DALAM PENENTUAN HARGA JUAL ROTI DAN KUE DI MADURA: SEBUAH STUDI FENOMADUROLOGI - Rusmiati Ningsih; Robiatul Robiatul Auliyah; Achdiar Redy Setiawan (Distribusi - Journal of Management and Business, 2018)
This research seeks to uncover the practice of selling bread and cakes in Madura. This research using qualitative methods in the process of discovery the answers, and also phenomadurological approach in the process of analysis the extending about awareness of "Aku" with Madura culture. The approach is chosen because researchers need the depth methods to reveal the reality behind the phenomenon. The research is also need the informants, there are two main informants is home business owners amounted to 2 people, as well as supporting informants that the customer amounted to 4 people. This research site was conducted at the place of home business in Jl. K Lemah Duwur Bangkalan. The results showed that the practice of determining the price of bread and cookies that occur based on the calculation of raw material costs and factory overhead costs. In addition, there are costs which made bythe invisible mark up. After exploring the cost and the markup, there is a determination of the values contained in the selling price. The values contained namely Po Sapo Esempay (Solidarity) realized with a sense of mutual help, family/ friend as an advantage over the matter, an expression of care, sharing the happiness, trust to others and also to give an attention to the situation around us. Another value that is contained is Sokkla (Religiousity), which materialized with their interests for the charity, belief in God's justice, charity as savings in the Hereafter, and surrender to God.